Assessment of Municipal Solid Waste Management Practices in Bahawalpur City, Pakistan: Assessment of Municipal Solid Waste Management Practices in Bahawalpur City, Pakistan - Khan, Asad Ali; Mohsin, Muhammad; Nasar-u-Minallah, Muhammad; Barkat, Tasleem (International Journal of Economic and Environmental Geology, 2024)
Solid waste management is a global issue persisting in most of the developing countries like Pakistan. Current study briefly appraises the management and practices of municipal solid waste (MSW) in Bahawalpur City. Data were collected from different sources by using an in-depth interview and questionnaire tool. The findings reveal that domestic organic waste accounts for about 35.32% followed by debris, dirt and construction material waste (30.89%). About 273.69 tons solid waste is generated on daily basis whereas only 218.95 tons per day is collected and disposed. The collection rate of MSW varies from 61% to 80% in the city. The service coverage area was about 70%. The total sanitary staff was also very limited (735) as compared to the increasing population and served only 75% population of the Bahawalpur. The equipment and machinery used for MSW collection and disposal operation were also limited and out of fashion which were needed to be replaced. There is no proper landfill for disposal of solid waste which is openly thrown at five dumping sites and burned. This situation further creates many environmental and health issues. Recycling is almost absent in the city and behavior of the inhabitants also adds to an ineffective solid waste management in the city. It is necessary to create awareness among the people about bad effects of improper dumping of solid waste and the need to tackle this problem.